2020
DOI: 10.3390/cells9051090
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of mTORC1 Signaling Pathway by HIV-1

Abstract: Mammalian target of rapamycin complex 1 (mTORC1) is a master regulator of cellular proliferation and survival which controls cellular response to different stresses, including viral infection. HIV-1 interferes with the mTORC1 pathway at every stage of infection. At the same time, the host cells rely on the mTORC1 pathway and autophagy to fight against virus replication and transmission. In this review, we will provide the most up-to-date picture of the role of the mTORC1 pathway in the HIV-1 life cycle, latenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 136 publications
(179 reference statements)
0
29
0
Order By: Relevance
“…HIV-1 Env can activate the MTORC1 complex resulting in efficient viral replication and viral production. In fact, HIV-1 infection increases MTORC1 activity in both productively infected and bystander cells (Akbay et al, 2020).…”
Section: Autophagy and Early Hiv-1 Infection In Macrophages And Dendritic Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV-1 Env can activate the MTORC1 complex resulting in efficient viral replication and viral production. In fact, HIV-1 infection increases MTORC1 activity in both productively infected and bystander cells (Akbay et al, 2020).…”
Section: Autophagy and Early Hiv-1 Infection In Macrophages And Dendritic Cellsmentioning
confidence: 99%
“…Another drug, LY 294002 that inhibits PIK3 class I as well as MTORC1, suppresses viral infection of macrophages in post-entry and post-reverse transcription steps prior to HIV-1 gene expression (François and Klotman, 2003). Pan-inhibitors of MTORC1 neutralize HIV-1 infection by interfering with viral entry in humanized mouse in vivo models, since these inhibitors decrease CCR5 levels at the cell-surface of target cells, and also act during viral transcription (Heredia et al, 2015;Akbay et al, 2020). Likewise, other research showed that HIV-1 gp41-induced apoptosis is mediated by caspase-3-dependent mitochondrial production of ROS (Garg and Blumenthal, 2006), which acts as a stimulus to sustain the autophagy process (Levonen et al, 2014;Filomeni et al, 2015).…”
Section: The Effect Of Autophagy Modulation In the Early Steps Of Hiv-1 Infectionmentioning
confidence: 99%
“…HIV infection is associated with an elevated risk of developing AIDS-defining cancers, including a number of B-cell lymphomas [ 9 , 10 ]. Even though a current antiretroviral therapy is quite efficient, a high incidence of HIV-1-associated malignancies persists and the mechanism of development of these diseases is largely unclear [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This miRNA targets AKT and mTOR, central components of the mTORC1 complex [76]. A double suppression of the mTOR pathway helps in the early stage of HIV infection, blocking the entry to the cell through CCR5 recycling and interfering with induced and basal transcription [77]. Although only one DE miRNA is regulated similarly in HESN compared to our LTNP patients, it should be noticed that resistance mechanisms in HESN may differ from those of LTNPs since the latter regulates disease progression and HESN is probably involved in HIV-1 acquisition.…”
Section: Discussionmentioning
confidence: 99%